Strengthening Public School Culture: Integration of Local Wisdom, Religious Values, and Universal Values - Jamaluddin, Jamaluddin; Manda, Dea Alifia (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study focuses on integrating local wisdom, religious values, and universal values. This study aims at revealing various secondary school cultures in public schools. This study employed a qualitative method with a case study design at Junior High School SMPN 7 Muaro Jambi. Data was collected using observation, in-depth interviews, and document study techniques. The collected data were analyzed using an interactive model, including data condensation, presentation, and verification. Triangulation techniques, extended observations, and member checks are employed to increase the validity of the data. The study revealed that five school cultures still characterize school managerial life: Gotong Royong (cooperation), Musyawarah (deliberation), Islamic Ritual, Clean and Healthy, and Discipline. These five cultures are manifestations of adherence to local values (indigenousity), religious values, and universal values. Combining these three integrated sources of values is a distinctive pattern of school culture that becomes the foundation for developing school quality at public schools at SMPN 7 Muaro Jambi. This research implies that integrating local, religious, and universal values in school culture enriches learning and prepares students for a globally complex world.